Impact of transcranial magnetic stimulation on the symptom profile of major depressive episode. (June 2019) - May, Tamara; Pridmore, Saxby
Objectives: This study aimed to explore the effects of a four-week course of transcranial magnetic stimulation (TMS) on the following symptoms of major depressive episode (MDE): mood, work activities, health concerns, guilt, anxiety and retardation. Method: Patients underwent 20 daily sessions of 10 Hz TMS (two sets of 10 daily treatments separated by two days of rest). The six-item Hamilton Depression Rating Scale (HAMD-6) was administered before and after treatment. Remission was operationalised as a HAMD-6 score of <4. Descriptive statistics and t -tests were used to compare pre/post scores on HAMD-6 subscales, and logistic regression was used to understand symptoms that predicted remission/non-remission. Results: There were 104 participants (79 female; 76%), with a mean age of 44.6 years ( SD =15.7 years). There was a significant improvement in the whole sample and in remitters ( n =70) on all subscales. However, those who failed to remit did not achieve significant reductions in 'health concerns' and 'retardation'. There were no difference in age and sex between remitters and non-remitters. Also, there were no significant differences between the remitters and non-remitters on the pretreatment depression symptom profiles. No predictors of response were identified, as expected. Conclusions: TMS has the ability to reduce all listed MDE symptoms. No pretreatment MDE symptom profile was identified which might carry prognostic value.